(untitled) (LACCEI, 2024)
The objective of this study is to determine the influence of the use of mobile applications on the purchasing behavior of fast-food consumers in the province of Trujillo, where companies have had to adapt to the digital era to survive. For this purpose, applied research was carried out, with a quantitative approach, cross-sectional, non-experimental design, and correlational scope. The survey was used as a technique and the questionnaire as an instrument, and the study population consisted of the inhabitants of the province of Trujillo, aged between 18 and 64 years, with a sample of 267 people. Consequently, the results showed that there is a significant relationship between the use of mobile applications and purchasing behavior with a Spearman’s Rho of 0.157 and confirmed the influence between both variables with 43.6% according to Nagelkerke coefficient. In conclusion, with the increasing use of mobile applications, the purchase behavior improves therefore, the purchase process improves, which is positive for brands because they benefit monetarily.